MOTIVASI KERJA MENCERMIKAN KEBERHASILAN KINERJA PEGAWAI - Dimas Prasetiyo; Ana Kadarningsih (Pusat Riset dan Inovasi Nasional, 2023)
The development of human resources in organizations involves individuals, employees making changes from traditional to modern thinking creatively and critically, so that employees improve their performance. Employee performance is closely related to the image of the institution so special attention is needed to improve employee performance. Of course, this is done by the Losari Health Center, Pemalang Regency, Central Java to improve the performance of its employees. The goal of the Losari Health Center is achieved. Technically, this research uses a quantitative method, namely a way of expressing phenomena through numerical data, then it is analyzed mathematically, the results are used as the basis for drawing conclusions. The research results are described as an approach to reveal research facts. The facts above are intended for a discussion of a problem at the Losari Health Center and identify the influence of work discipline, work motivation and work environment variables on employee performance. After doing the research, it can be seen that work discipline, work motivation and work environment simultaneously affect employee performance. Research results in the variable work discipline can have a significant positive effect on employee performance. In the work motivation variable, work motivation can have a significant positive effect on employee performance, which can be interpreted. Finally, the work environment variable shows that the work environment can have a significant and positive influence on employee performance.